Daily Rhythms of Female Self-maintenance Correlate with Predation Risk and Male Nest Attendance in a Biparental Wader - Brynychová, Kateřina; Šálek, Miroslav E; Vozabulová, Eva; Sládeček, Martin (Journal of biological rhythms, 2020)
Parents make tradeoffs between care for offspring and themselves. Such a tradeoff should be reduced in biparental species, when both parents provide parental care. However, in some biparental species, the contribution of one sex varies greatly over time or between pairs. How this variation in parental care influences self-maintenance rhythms is often unclear. In this study, we used continuous video recording to investigate the daily rhythms of sleep and feather preening in incubating females of the Northern Lapwing (Vanellus vanellus), a wader with a highly variable male contribution to incubation. We found that the female's sleep frequency peaked after sunrise and before sunset but was low in the middle of the day and especially during the night. In contrast, preening frequency followed a 24-h rhythm and peaked in the middle of the day. Taken together, incubating females rarely slept or preened during the night, when the predation pressure was highest. Moreover, the sleeping and preening rhythms were modulated by the male contribution to incubation. Females that were paired with more contributing males showed a stronger sleep rhythm but also a weaker preening rhythm. If more incubating males also invest more in nest guarding and deterring daylight predators, their females may afford more sleep on the nest during the day and preen more when they are off the nest. Whether the lack of sleep in females paired with less caregiving males has fitness consequences awaits future investigation.
Keywords: Fathers; Male; biparental incubation; Charadriiformes; Circadian Rhythm; sleep; preening; hnízdění; otcové; Animals; spánek; Nesting Behavior; Mothers; Predatory Behavior; zvířata; nest predation; cirkadiánní rytmus; mužské pohlaví; péče o zevnějšek u zvířat; Sleep; matky; predátorské chování; ženské pohlaví; Female; Northern Lapwing Vanellus vanellus; shorebirds; Grooming